2010
DOI: 10.1111/j.1540-8159.2010.02874.x
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Myocardial Infarction Case that Survived An Out‐of‐Hospital Cardiac Arrest in Which Prominent Ischemic J Waves Were Documented

Abstract: We describe a case of a myocardial infarction, in which prominent ischemic J waves were documented during recurrent ventricular fibrillation attacks. The patient was referred to our hospital to treat an out-of hospital cardiac arrest. Although the 12-lead electrocardiogram obtained just after the first cardioversion did not show any apparent J waves, a J wave-like steep downsloping type ST-segment elevation associated with q waves in the inferior leads was documented during multiple episodes of ventricular fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…JWS is characterized by the appearance of a prominent electrocardiographic J wave with a risk of ventricular fibrillation (VF), including inherited Brugada syndrome (BrS), traditional repolarization syndrome (ERS), idiopathic ventricular fibrillation (IVF), and acquired arrhythmias linked to STEMI and hypothermia. Myojo et al 7 reported that ischaemic J waves were observed during recurrent VF attacks in a patient with myocardial infarction, which implied that the appearance of J waves could be an important marker for lethal arrhythmias in acute ischaemia. Generally, J waves can be classified as inherited and acquired patterns.…”
Section: Introductionmentioning
confidence: 99%
“…JWS is characterized by the appearance of a prominent electrocardiographic J wave with a risk of ventricular fibrillation (VF), including inherited Brugada syndrome (BrS), traditional repolarization syndrome (ERS), idiopathic ventricular fibrillation (IVF), and acquired arrhythmias linked to STEMI and hypothermia. Myojo et al 7 reported that ischaemic J waves were observed during recurrent VF attacks in a patient with myocardial infarction, which implied that the appearance of J waves could be an important marker for lethal arrhythmias in acute ischaemia. Generally, J waves can be classified as inherited and acquired patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that J-waves are associated with the incidence of ventricular arrhythmias in patients with Brugada syndrome, myocardial infarction, and nonischemic cardiomyopathy. [1][2][3][4][5][6][7] Consumption of fish oil containing large amounts of n-3 polyunsaturated fatty acids (PUFAs) including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) has been shown to reduce cardiovascular events and death. 8) A 45% reduction in sudden cardiac death was reported with the consumption of n-3 PUFAs in the GISSI-Prevenzione trial, 9) and EPA combined with statin therapy significantly reduced major coronary events in hypercholesterolemic patients with established coronary artery dis-ease in the JELIS trial.…”
mentioning
confidence: 99%
“…A prominent J wave merging into a steep downsloping ST segment without an initial upsloping phase is termed the J wave-like ST-segment elevation [ 6 ]. Several studies have suggested that some cases of acute myocardial infarction (AMI) are mechanistically linked to this distinctive ST-segment elevation pattern [ 7 ]. However, to the best of our knowledge, the J wave-like ST-segment elevation on the ECG has been rarely reported to occur in patients with ICH.…”
Section: Discussionmentioning
confidence: 99%